Nanoscale surface patterning of diamond utilizing carbon diffusion reaction with a microstructured titanium mold. Issue 1 (2018) - Yan, Jiwang; Imoto, Yuji
Abstract: A novel method was proposed for generating nanoscale surface patterns on single-crystal diamond by carbon diffusion with a microstructured titanium mold under controlled temperature and pressure. The depth, geometry, and surface integrity of the fabricated patterns were investigated by laser micro-Raman spectroscopy and white-light interferometry, and the titanium molds were analyzed by energy dispersive X-ray spectroscopy. The results showed that at specific temperatures and pressures, three-dimensional patterns with a depth of tens of nanometers and sloped/curved walls could be generated on a diamond surface after a few minutes, without causing any surface graphitization. The intensity profile and penetration depth of carbon atoms into the titanium were experimentally measured.